Gonial angle, antegonial angle, and bigonial breadth among Chinese and Batak ethnic groups: A panoramic radiographic analysis - Perdani, Mustika Lili; Wilvia, Wilvia; Tabhita, Kanaya; Ishak, Ishfahani Suriadi; Perangin-angin, Meika Maharani Br; Pasaribu, Tulus; Desta, Maorina; Tanjung, Dian Soraya; Purba, Member Reni (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Mandibular morphology is a key aspect of antropometry and dentistry, reflecting anatomic variations influenced by genetic, ethnic, and environmental factors. Parameters such as bigonial width, gonial angle, and antegonial angle serve as primary indicators in mandibular morphometric analysis, with applications in orthodontics, maxillofacial surgery, and forensic identification. Population-based morphometric data for local Indonesian groups remain limited. This study addresses this gap by examining mandibular characteristics in Batak and Chinese ethnic groups. This study aimed to compare bigonial width, gonial angle, and antegonial angle between Batak and Chinese groups using panoramic radiographs. Methods: This cross-sectional, observational, analytic study included 50 subjects (25 Batak and 25 Chinese) at RSGM Prima. Measurements were performed with ImageJ software and analyzed using Shapiro-Wilk normality test, Levene homogeneity test, and independent t-test. Results: No statistically significant differences were found in gonial angle (p=0.665), antegonial angle (p=0.218), or bigonial width (p=0.328) between the groups. Conclusion: No significant differences exist in gonial angle, antegonial angle, or bigonial width between Batak and Chinese groups. Mandibular morphometric variations are not determined solely by ethnicity. These parameters should be integrated with other anthropologic markers and primary identification methods for greater accuracy in clinical and forensic applications.